Nonequilibrium Statistical Physics of Small Systems 2013
DOI: 10.1002/9783527658701.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Large Deviation Approach to Nonequilibrium Systems

Abstract: The theory of large deviations has been applied successfully in the last 30 years or so to study the properties of equilibrium systems and to put the foundations of equilibrium statistical mechanics on a clearer and more rigorous footing. A similar approach has been followed more recently for nonequilibrium systems, especially in the context of interacting particle systems. We review here the basis of this approach, emphasizing the similarities and differences that exist between the application of large deviat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 62 publications
1
102
0
Order By: Relevance
“…Indeed, the cusp in ψ ω (λ) when N → ∞ implies that the region of the large deviation function between the entropy rates σ * h and σ * l is connected by a Maxwell construction (or a tie-line) with a slope λ * . The LF transform of ψ ω (λ) only provides the convex envelope of I(σ), but in the limit of large τ , I(σ) must converge to that envelope [22]. Further, as illustrated in Fig.…”
mentioning
confidence: 99%
“…Indeed, the cusp in ψ ω (λ) when N → ∞ implies that the region of the large deviation function between the entropy rates σ * h and σ * l is connected by a Maxwell construction (or a tie-line) with a slope λ * . The LF transform of ψ ω (λ) only provides the convex envelope of I(σ), but in the limit of large τ , I(σ) must converge to that envelope [22]. Further, as illustrated in Fig.…”
mentioning
confidence: 99%
“…Moreover, this 'Level 2.5' formulation allows to reconstruct any time-additive observable of the dynamical trajectory via its decomposition in terms of the empirical densities and of the empirical flows, and is thus closely related to the studies focusing on the generating functions of time-additive observables via deformed Markov operators, that have attracted a lot of interest recently in various models [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. More generally, the idea that the theory of large deviations is the appropriate language to analyze non-equilibrium dynamics has been emphasized from various perspectives (see the reviews [16,25,26,[30][31][32][33] and the PhD Theses [4,13,34,35] or HDR Thesis [36]).…”
Section: Introductionmentioning
confidence: 99%
“…While the region (ii) of universal typical fluctuations has been traditionally the main focus of studies for various physical observables, the theory of large deviations (iii) is nowadays considered as the unifying language for the statistical physics of equilibrium, non-equilibrium and dynamical systems (see the reviews [8][9][10] and references therein). In particular, the large deviations with respect to the large time limit of dynamical trajectories has produced an appropriate statistical physics approach for various Markovian processes (see the reviews [11][12][13][14][15][16][17] and the PhD Theses [18][19][20][21] and the HDR Thesis [22]). However the recent huge activity on large deviations in the field of random matrices has shown that the maximal eigenvalue [23][24][25][26][27][28] and many other observables involving the eigenvalues [29][30][31][32][33][34][35][36][37][38][39] display asymmetric scaling in large deviations : the probability P N (u) to observe bigger values than typical u > u typ and smaller values than typical u < u typ are governed by two different scalings D ± N (for instance two different power-laws D ± N = N θ± ) and two rate functions I ± (u)…”
Section: Introductionmentioning
confidence: 99%